Empirical Mode Decomposition Profilometry: Small-Scale Capabilities and Comparison to Fourier Transform Profilometry - Lagubeau, G (OPTICAL SOC AMER, 2015)
We present the empirical mode decomposition profilometry (EMDP) for the analysis of fringe projection profilometry (FPP) images. It is based on an iterative filter, using empirical mode decomposition, which is free of spatial filtering and adapted for surfaces characterized by a broadband spectrum of deformation. Its performances are compared to Fourier transform profilometry, the benchmark of FPP. We show both numerically and experimentally that using EMDP improves strongly the profilometry small-scale capabilities. Moreover, the height reconstruction distortion is much lower: the reconstructed height field is now both spectrally and statistically accurate. EMDP is thus particularly suited to quantitative experiments. (C) 2015 Optical Society of America